Navigating the seamless environment in the global supply chain: implications for Canadian regions and workers. (1st July 2007) - Penny Gurstein
Abstract : When work is 'boundless' and 'seamless' where and how do workers' lives intersect with the space-time continuum of place-based communities? Who and what are they accountable to? Telemediation is fragmenting work across increasingly complex, transnational networks. Workers in these networks must negotiate through a multitude of temporal, contractual and trans-cultural milieus. This paper traces the trajectory of the work experience using case studies of telemediated work relationships in various points in the global supply chain and analyses the implications of telemediated spaces for the quality of workers' lives. Drawing on an analysis of case studies conducted by the EMERGENCE Canada project, this paper argues that telemediated work represents a shift in the scale at which many aspects of daily life unfold, and that some of the assumptions upon which workers' lives are governed must be reconsidered.